Efficient electrospray deposition of surfaces smaller than the spray plume - Sarah H. Park; Lin Lei; Darrel D’Souza; Robert Zipkin; Emily T. DiMartini; Maria Atzampou; Emran O. Lallow; Jerry W. Shan; Jeffrey D. Zahn; David I. Shreiber; Hao Lin; Joel N. Maslow; et al. (Nature Communications, 2023)
Abstract Electrospray deposition (ESD) is a promising technique for depositing micro-/nano-scale droplets and particles with high quality and repeatability. It is particularly attractive for surface coating of costly and delicate biomaterials and bioactive compounds. While high efficiency of ESD has only been successfully demonstrated for spraying surfaces larger than the spray plume, this work extends its utility to smaller surfaces. It is shown that by architecting the local “charge landscape”, ESD coatings of surfaces smaller than plume size can be achieved. Efficiency approaching 100% is demonstrated with multiple model materials, including biocompatible polymers, proteins, and bioactive small molecules, on both flat and microneedle array targets. UV-visible spectroscopy and high-performance liquid chromatography measurements validate the high efficiency and quality of the sprayed material. Here, we show how this process is an efficient and more competitive alternative to other conformal coating mechanisms, such as dip coating or inkjet printing, for micro-engineered applications.